Parametric studies of the NSM FRP strips shear strength contribution to a RC beam - Bianco, V. (2011)
A three dimensional mechanical model was recently developed to simulate the shear strength contribution provided by a system of Near Surface Mounted (NSM) Fiber Reinforced Polymer (FRP) strips to a Reinforced Concrete (RC) beam throughout its loading process. It was developed fulfilling equilibrium, kinematic compatibility and constitutive laws of both materials, concrete and FRP, and local bond between themselves. In the present paper, that model is first appraised on the basis of some of the most recent experimental results and then is applied to carry out parametric studies. The influence of each of the involved parameters on the contribution provided by a system of NSM FRP strips to the shear strength of a RC beam is investigated. The results of those studies are presented along with the main findings.